2013
DOI: 10.1016/j.resp.2012.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory responses during and following exposure to a hypoxic challenge in conscious mice deficient or null in S-nitrosoglutathione reductase

Abstract: Exposure to a hypoxic challenge increases ventilation in wild-type (WT) mice that diminish during the challenge (roll-off) whereas return to room air causes an increase in ventilation (short-term facilitation, STF). Since plasma and tissue levels of ventilatory excitant S-nitrosothiols such as S-nitrosoglutathione (GSNO) increase during hypoxia, this study examined whether (1) the initial increase in ventilation is due to generation of GSNO, (2) roll-off is due to increased activity of the GSNO degrading enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(71 citation statements)
references
References 95 publications
5
66
0
Order By: Relevance
“…As reviewed by Palmer and colleagues (11,18), studies in humans found that HVRs are greater in females, equal in females and males, or that women have a lower HVR and hypercapnic drive than men. Disparate findings have also been generated in rats.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As reviewed by Palmer and colleagues (11,18), studies in humans found that HVRs are greater in females, equal in females and males, or that women have a lower HVR and hypercapnic drive than men. Disparate findings have also been generated in rats.…”
Section: Discussionmentioning
confidence: 99%
“…First, the expression of HVR and shortterm potentiation (STP) are absent in conscious mice with bilateral carotid sinus nerve transection (39), supporting a role of carotid body primary glomus cells/ chemoafferents in these responses. As such, the potential release of S-nitrosothiols from eNOS-positive glomus cells (11) and subsequent activation of chemoafferent terminals may contribute to the initiation of HVR, whereas S-nitrosothiols generated from red blood cell hemoglobin (see subsequent text) do not appear to be vital for initiation of the HVR (39). Second, ventilatory roll-off during the hypoxic challenge is absent in conscious GSNOR 1/2 or GSNO 2/2 mice (11), clearly suggesting that roll-off is due to enhanced catabolism of GSNO in the carotid body and/or central structures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations